Breast Care Knowledge and Attitudes in Special Women at the Barru Regional General Hospital, Barru Regency, South Sulawesi - Sima, Yenni; Ruagadi, Henry A.; Ngguna, Yakin; Andarwulan, Setiana; Wahyuni, Ria; Djaha, Yohan Traiyanus; Syafri, Muhammad (International Journal of Health Sciences, 2024)
Breast care during the postpartum period is a necessity for mothers who have just given birth. The postpartum period itself is six weeks or 40 days after delivery. During the postpartum period, breast care is a very important action to care for the breasts, especially to facilitate the release of breast milk (ASI). Swollen breasts usually occur in the first days of a baby's birth. Data obtained from Barru Hospital showed five cases of swollen breasts. The aim of this study was to determine the relationship between postpartum mothers' knowledge and attitudes towards breast care at Barru Hospital. This research uses a correlation analytical method with a cross sectional approach, data collection techniques using questionnaires with respondents namely postpartum mothers who receive services at Barru Hospital. Data analysis uses univariate analysis to test respondents' knowledge and attitudes and bivariate analysis to determine the relationship between variables. The results of univariate research with frequency distribution show that some respondents (52.5 %) have less knowledge, the attitude category shows that some respondents (52.5%) have an unsupportive attitude. The results of bivariate analysis with Chi-Square distribution obtained a value of 0.01 (p-value < 0.05). The results of the bivariate analysis showed that very few of the respondents (19%) were 4 people with little knowledge and a supportive attitude. The conclusion of this research is that there is a relationship between postpartum mothers' knowledge and attitudes towards breast care at Barru Hospital. Advice to health workers to carry out continuous outreach and education about breast care.